Hyperoxemia reduces cerebrovascular accidents post coronary artery bypass graft surgery: a retrospective cohort study - Kempton, Hannah; Chong, Calum; Vlok, Ruan; Melhuish, Thomas; Holyoak, Rhys; White, Leigh (Journal of Emergency and Critical Care Medicine; Vol 4 (April 2020): Journal of Emergency and Critical Care Medicine, 2020)
Cerebrovascular accidents (CVAs) including strokes and transient ischaemic attacks (TIAs) form a major portion of perioperative morbidity in patients undergoing coronary artery bypass graft (CABG) surgery. The aim of this article was to: (I) to examine the relationship between providing increased intraoperative partial pressure of arterial oxygen (PaO2) and the risk of perioperative CVA following CABG surgery; (II) to examine the relationship between intraoperative PaO2 and other perioperative adverse outcomes. This was a retrospective cohort study involving 2,253 consecutive CABG patients located within a single cardiothoracic unit of a tertiary hospital. All patients underwent CABG surgery. A multivariate analysis was undertaken to assess the relationship between the PaO2 (intra-operative mean and nadir) and its associated risk of perioperative CVA. Results were reported as odds ratios (OR) with 95% confidence interval (95% CI). There was a significant (but clinically limited) inverse correlation between average intra-operative PaO2 and reducing peri-operative CVA (OR 0.99; P=0.029; 95% CI: 0.98–1.00), indicating a reduction in stroke risk with increasing PaO2. There was no significant association with PaO2 nadir and CVA. There was no significant association between increasing hyperoxia and the following adverse events: pneumonia, prolonged postoperative ventilation, perioperative myocardial infarction or cardiac arrest, sternal wound infection, sepsis and renal failure. We report a significant inverse correlation between increasing average intra-operative PaO2 and reducing peri-operative CVA. Further, hyperoxia was not associated with any adverse effects or infective outcomes. This finding is likely to have preventative and therapeutic implications through reducing stroke risk.